Third-Trimester Stillbirths: Correlative Neuropathology and Placental Pathology - Chang, Kenneth T.E.; Keating, Sarah; Costa, Stacy; Machin, Geoffrey; Kingdom, John; Shannon, Patrick (Pediatric and developmental pathology, 2011)
Although in recent years placental pathology has been the subject of a wealth of detailed descriptions and diagnostic categorization, systematic correlation of these conditions with the pathology of stillbirth has not been attempted. We examine the relationship between specific inflammatory, maternal, and fetal vascular pathologies and the central nervous system pathology and histological indicators of fetal compromise. Our design was a retrospective case series of 37 3rd-trimester intrauterine fetal deaths. In general, mixed placental pathologies were the rule, with three quarters of the placentas demonstrating combinations of maternal vascular pathology, fetal vascular pathologies, umbilical cord abnormalities, or inflammatory lesions. The range of brain pathology was limited to acute, severe congestion, white matter edema, and neuronal karyorrhexis (pontosubicular necrosis with or without neuronal karyorrhexis at other sites). Established periventricular leukomalacia was present in only 2 cases. The presence of neuronal karyorrhexis or white matter gliosis was correlated with the presence of a high-grade inflammatory lesion and with fetal thymic involution. Neuronal karyorrhexis, but not white matter gliosis, correlated as well with histologically established fetal vascular lesions in the placenta, even once the effect of inflammation was accounted for. Gliosis also correlated with inflammation, meconium staining, and thymic involution. Central nervous system injury may be the end result of complex placental pathologies, and neuronal injury may be a consequence of the fetal inflammatory response. The correspondence between the time courses of histological features of chorioamnionitis, neuronal karyorrhexis, and thymic involution points to irreversible central nervous system injury being common 12–48 hours prior to in utero demise.